Cesar Chavez : autobiography of La Causa - Levy, Jacques E.; Chavez, Cesar, 1927-1993. (Minneapolis : University of Minnesota Press, 2007)
Mexican-American civil rights and labor activist Cesar Chavez (1927-1993) comes to life in this vivid portrait of the charismatic and influential fighter who boycotted supermarkets and took on corporations, the government, and the powerful Teamster's Union. Jacques E. Levy gained unprecedented access to Chavez and the United Farm Workers in writing this account of one of the most successful labor movements in history - which also serves as a guidebook for social and political change.
Seeds in the desert -- Uprooted and adrift -- Crusaders in the barrios -- The birth of a union -- Victory in the vineyards -- New fields, old enemies -- Target for destruction.
Originally published in 1975 by W. W. Norton and Company, Inc.
Includes index.
Includes bibliographical references (p. 548) and index.
Keywords: Chavez, Cesar, -- 1927-1993.; United Farm Workers; Migrant agricultural laborers -- United States -- Biography; Labor leaders -- United States -- Biography; Mexican Americans -- Biography